COMMUNITY PARTICIPATION IN MANAGEMENT OF HOUSHOLD WASTE STUDY IN PARTNERS OF DALANG COLLECTION WASTE BANK - ", Rosyidah; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This background in this research start from garbage proble that often happened in Pekanbaru City that hard to handle. Later found there is a waste bank built from government which is named Dalang Collection Waste Bank. This garbage bank has several partners who joined and participated. Participation is one of the most interesting discussion and this research aims to examine what are the factors that make people willing to join and participate in the management of household waste and what kind of participation that exist in Dalang Collection Waste Bank, because with good and proper waste management, it will have a very good impact on the existing garbage problem in Pekanbaru City. In this research there are result that states that there is a form of community participation in waste and doing activities from 4R program. According to the survey, the level of participation of respondents are calculated in medium, and from 41 respondents in this study, they have their own reasons and factors in terms of community participation of waste management, and to find out what factors affect the partners to participate in Dalang Collection Wate Bank.Keywords : Participation, Waste Bank Partners, Pekanbaru